Molecular target identification of two Coleus amboinicus leaf isolates toward lung cancer using a bioinformatic approach and molecular docking-based assessment - Winarto Haryadi, Kasta Gurning,, Endang Astuti (Journal of Applied Pharmaceutical Science, 2024)
Lung cancer raises a serious concern because of its position as the second global deathliest disease in both men and women. Conventional treatments emphasize chemotherapy and radiation or their combination, which is considered to be ineffective due to harmful side effects in patients. In this work, we did a bioinformatic investigation using the pharmacological network and molecular docking approaches to evaluate the potency of natural compounds isolated from the leaves of Coleus amboinicus, Lour, i.e., 16-hydroxy-7α-acetoxyroyleanone and 16-acetoxy- 7α-hydroxyroyleanone. The activity of both active compounds against lung cancer was predicted using disease databases and genes. A total of 77 core targets were identified from the analysis using STRING and built using Cytoscape. Gene ontology, and Kyoto encyclopedia of genes, and genome analysis of cancer pathways targeting PGTS2 and peroxisome proliferator-activated receptor gamma were employed because of their critical functions in cancer therapy. The validated molecular docking analysis illustrates the possibility of interactions that occur between active compounds of target proteins in the treatment of lung cancer. This research has not yet been able to demonstrate its potential in the treatment of lung cancer, and further research is needed to prove it through in vitro and in vivo examinations before pre-clinical and clinical tests in the future.
Keywords: Lung cancer, bioinformatic, molecular docking, PTGS-2, PPARG